Economic evaluation of generation and storage solutions in low voltage end user installations - Rúben A. Soares (2015)
Storage technologies are expected to assume an increasing relevance in the next few years, given the widespread number of available options, the possible applications and the reduction of investment costs. Therefore and apart from the well-known hydro pumping stations, the installation of storage is being considered as an increasingly viable option namely in distribution networks and also in end user installations. This paper reviews the recently passed Portuguese legislation on self-consumption and details a model to evaluate the economic interest of installing batteries together with PV panels according to several possible business models. The simulations suggest that the tariffs currently applied and the investment costs turn these options still not attractive so that a final simulation was developed to evaluate the break even value of the tariffs to turn the investments on storage paid in a reasonable horizon.